1978
DOI: 10.1136/jcp.31.5.444
|View full text |Cite
|
Sign up to set email alerts
|

Urine xanthine oxidase activity in urinary tract infection.

et al.

Abstract: SUMMARY Xanthine oxidase (XO) activity was found to be negligible in sterile human urines (less than 480 units, as presently defined, per litre). Significant XO (Brenner and Gilbert, 1963;Bank and Bailine, 1965;Mirabile et al., 1966;Montgomerie et al., 1966;Gault et al., 1967;Kallet and Lapco, 1967;Roberts et al., 1967). The diagnostic value of these methods is limited by the potential derivation of the respective urinary enzymatic activities from renal and urinary tract tissues and from blood cells and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…XO enzyme is confined in man mainly to the liver; a significant but lower activity has been found also in jejunal mucosa and colostrum; on the other hand, the kidney, prostate, and blood elements, as well as normal serum, are virtually devoid of XO activity [ 9 – 14 ]. Indeed, we showed that urine XO activity was increased in patients with UTI, conforming to previously reported results, indicating that plasma XO is transferred to the urine, probably due to its low molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…XO enzyme is confined in man mainly to the liver; a significant but lower activity has been found also in jejunal mucosa and colostrum; on the other hand, the kidney, prostate, and blood elements, as well as normal serum, are virtually devoid of XO activity [ 9 – 14 ]. Indeed, we showed that urine XO activity was increased in patients with UTI, conforming to previously reported results, indicating that plasma XO is transferred to the urine, probably due to its low molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…100,107 XOR has been shown to be elevated in tissue and blood under certain conditions such as viral hepatitis, 108 intestinal infection, 109 jaundice, 108,110 renal inammation, 111 and ischemia/reperfusion injury. 101,112,113 XO has also been observed in urine during UTI, 114,115 but there has generally not been much focus on XO in urine or in relation to UTI.…”
Section: Enzymatic Markersmentioning
confidence: 99%
“…This enzyme is involved in the pathogenesis of tissue injury by the production of superoxide anion radicals and hydrogen peroxide or both [16,17] . Or may be indicating that plasma X.O is not transferred to the urine, probably due to its high molecular weight [18] . The studies by Borges et al, 2002, had used xanthine oxidase inhibitors as a means to prevent (CRF) in animals, also showed that the X.O levels in blood had significantly increased in different pathological cases, like aging, ischemia reperfusion, inflammation and cancer, and that reactive oxygen species generated in the enzymatic process were involved in oxidative damage [19] .…”
Section: -Xanthine Oxidase Activity (Xo)mentioning
confidence: 99%